Construction filler
A filler composition of clinker ash, fly ash, sand, and cement with controlled water content addresses fluidity and bleeding issues, enhancing its suitability for civil engineering while minimizing hazardous substance elution.
Patent Information
- Application Number
- JP2021012844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Clinker ash, despite being easily procurable, has not been effectively used in fillers due to its high water absorption leading to decreased fluidity and increased bleeding, while fly ash, though fluid, poses risks of hazardous substance elution and low resistance to water.
A filler composition comprising clinker ash, fly ash, sand, and cement with controlled water content, optimized proportions, and inclusion of admixtures to enhance fluidity and suppress bleeding.
The filler achieves excellent fluidity and suppressed bleeding, suitable for civil engineering, with reduced hazardous substance elution and improved resistance to water, utilizing waste materials effectively.
Smart Images

Figure 0007664579000001 
Figure 0007664579000002 
Figure 0007664579000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a filler for civil engineering and construction work, which contains clinker ash, fly ash, sand, cement and water, and a construction method using said filler. [Background technology]
[0002] Fluidized soil made by mixing construction waste soil with water and cement is known as a filler used for backfilling, filling cavities, embankments, etc. in civil engineering and construction works. Fluidized soil is shipped from a dedicated manufacturing plant and is often used in urban areas, but in non-populated areas, the demand is not as high as in urban areas, so the profitability is low, and it is also difficult to procure raw materials such as construction waste soil. Therefore, there are few manufacturing plants and it is difficult to procure. In addition, it has been proposed to use fly ash, which is coal ash, as a filler material. Since fly ash is a fine powder with a spherical shape, using fly ash can increase the fluidity due to the ball bearing effect. Therefore, a filler made by mixing fly ash and cement has been proposed (see Patent Document 1). On the other hand, clinker ash, which is a type of coal ash, is a porous particle and has high water absorption, so when it is used as a filler, the fluidity decreases, and if the mixing water is increased to prevent the fluidity decrease, bleeding increases. For this reason, clinker ash has been used as a roadbed material (see Patent Document 2), but has rarely been used as a filler material. A self-hardening backfill material using fly ash, clinker ash, and cement has been proposed (see Patent Document 3), but this backfill material has a unit volume weight of 1.03 t / m 3As can be seen from the above, bleeding is suppressed by increasing the foaming rate using a foaming agent, and with materials with such a high foaming rate (so-called air mortar), there are problems such as the material sinking due to a decrease in foaming, low resistance to underwater separation due to vulnerability to water, and difficulty in filling voids containing groundwater or stagnant water. In addition, when fly ash is used, there is a risk of elution of Type 2 specified hazardous substances (heavy metals, fluorine, fluorine compounds, etc.) contained in the fly ash as specified in the Soil Contamination Countermeasures Act. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-227199 [Patent Document 2] JP 2003-49401 A [Patent Document 3] Japanese Patent Application Publication No. 4-182335 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a filler that uses clinker ash but has good fluidity and suppresses bleeding, making it suitable for use in civil engineering and construction work. [Means for solving the problem]
[0005] The present inventors have begun to study the use of clinker ash, a type of coal ash, as a filler for civil engineering and construction work. Since clinker ash is a material that is easily procured in the vicinity of thermal power plants, if clinker ash can be used as a filler material, filler for civil engineering and construction work can be manufactured even in areas where it is difficult to obtain fluidized treated soil. Furthermore, if clinker ash, which has a lower utilization rate than fly ash, can be used, by-products generated by coal-fired power generation can be effectively utilized and the amount of waste can be reduced. Therefore, when the inventors proceeded with the study of applying clinker ash to filler materials that have not been used much in the past, they found that a filler with good fluidity and suppressed bleeding can be obtained by combining clinker ash with sand.
[0006] That is, the present invention is specified by the following items. (1) A filler for civil engineering and construction work, comprising clinker ash, fly ash, sand, cement and water, the content of said water relative to the total content of said fly ash and cement being 150 volume percent or less. (2) The filler according to (1) above, characterized in that the total content of the clinker ash and sand is 45 to 65 mass% relative to the total content of the clinker ash, fly ash, sand and cement, and the content of the clinker ash relative to the total content of the clinker ash and sand is 50 to 90 mass%. (3) The filler according to (1) or (2) above, characterized in that the total content of the fly ash and cement is 35 to 55 mass% with respect to the total content of the clinker ash, fly ash, sand and cement, and the content of the cement with respect to the total content of the fly ash and cement is 20 to 40 mass%. (4) A filling method, comprising filling a cavity with the filler according to any one of (1) to (3) above. Effect of the Invention
[0007] The filler of the present invention contains clinker ash, fly ash, sand, cement and water, and thus has excellent fluidity and suppresses the occurrence of bleeding, making it suitable for civil engineering and construction work, despite the use of clinker ash. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The filler for civil engineering and construction work of the present invention is characterized by containing clinker ash, fly ash, sand, cement and water. Clinker ash is collected from coal ash remaining in a boiler at a coal-fired power plant that has fallen to the bottom of the boiler, and is mainly composed of silicon dioxide and aluminum oxide. The clinker ash in the present invention is not particularly limited as long as it is generally called clinker ash, but for example, clinker ash having a particle size in the range of 0.1 to 30 mm can be mentioned. Among them, a particle size in the range of 0.1 to 5 mm is preferable, and therefore a particle size distribution in which particles having a particle size of 5 mm or less are 80% by mass or more is preferable. Here, the particle size is a particle size measured by a sieving method, and a particle size in the range of 0.1 to 30 mm means that the particle passes through a 30 mm sieve but does not pass through a 0.1 mm sieve. A particle size of 80% by mass or more having a particle size of 5 mm or less means that the particles passing through a 5 mm sieve are 80% by mass or more. Fly ash is coal ash collected by a dust collector from the flue gas of a boiler at a coal-fired power plant, and is mainly composed of silicon dioxide and aluminum oxide. The fly ash in the present invention is not particularly limited as long as it is what is generally called fly ash. Fly ash that has had its particle size adjusted is usually used, but in the present invention, raw fly ash powder generated from a boiler can be used as is, and even products that do not meet the JIS standards can be used. Fly ash after particle size adjustment or products that meet the JIS standards may also be used. There is no particular limit to the specific surface area, and it can be, for example, 1200 cm 2 / g or more. The sand in the present invention is not particularly limited, and examples thereof include mountain sand, land sand, river sand, sea sand, crushed sand, and reclaimed sand. A suitable example is sand used in ready-mixed concrete as specified in JISA5308. As for the particle size, it is preferable that the sand passes through a 10 mm mesh sieve classified as fine aggregate as an aggregate for concrete, and passes through a 5 mm mesh sieve at a rate of 85% or more by mass. The cement in the present invention is not particularly limited, and examples thereof include various kinds of Portland cement, blast furnace cement, fly ash cement, and other mixed cements, and various kinds of special cements. Among them, blast furnace cement is preferable. The filler for civil engineering and construction work in the present invention is used to fill a certain space in civil engineering and construction work, and includes not only those generally called filler materials, but also those called backfill materials, middle filling materials, backfill materials, and embankment materials.
[0009] The filler of the present invention is characterized in that the water content relative to the total content of fly ash and cement in the filler is 150% by volume or less. By setting the ratio of water to fly ash and cement, which are powders with relatively small particle diameters among clinker ash, fly ash, sand, and cement, ([volume of water / (volume of fly ash+volume of cement)]) to 150% by volume or less, it is possible to suppress the occurrence of bleeding while improving fluidity. [Volume of water / (volume of fly ash+volume of cement)] is preferably 100% by volume or more. In addition, the water content relative to the total content of clinker ash, fly ash, sand, and cement is preferably 20 to 30% by mass. The filler of the present invention may contain other components in addition to clinker ash, fly ash, sand, cement, and water. Examples of other components include admixtures such as AE water reducing agents, high-performance water reducing agents, and high-performance AE water reducing agents, dolomite, stone powder, recycled crushed stone, and IGCC slag. The amount of these other components added is not particularly limited, but the amount of the admixture added is preferably 0.5 to 2.0 mass % based on the total content of fly ash and cement in the filler.
[0010] Conventionally, clinker ash has not been used as a filler material for civil engineering and construction work because it is difficult to improve fluidity and suppress bleeding at the same time. However, by using clinker ash and sand in combination with fly ash, cement and water, the filler of the present invention has excellent fluidity and bleeding properties. The filler of the present invention contains clinker ash, fly ash, sand, cement and water, and it is preferable that the total content of clinker ash and sand is 45 to 65 mass% relative to the total content of clinker ash, fly ash, sand and cement in the filler, and the content of clinker ash relative to the total content of clinker ash and sand is 50 to 90 mass%. In the present invention, the total content of clinker ash and sand relative to the total content of clinker ash, fly ash, sand and cement [(clinker ash content + sand content) / (clinker ash content + fly ash content + sand content + cement content)] and the content of clinker ash relative to the total content of clinker ash and sand [clinker ash content / (clinker ash content + sand content)] are within the above ranges, and even if the clinker ash content is high, the fluidity can be improved and the occurrence of bleeding can be suppressed. The total content of clinker ash and sand relative to the total content of clinker ash, fly ash, sand and cement is more preferably 45 to 55 mass%, and even more preferably 48 to 52 mass%. Moreover, the content of clinker ash relative to the total content of clinker ash and sand is more preferably 60 to 85 mass%, and even more preferably 70 to 85 mass%. In the present invention, since the inclusion of sand suppresses bleeding, when the contents of clinker ash and sand are within the above ranges, the effect of suppressing the occurrence of bleeding while improving fluidity is further improved. In addition, since clinker ash does not contain much harmful substances such as heavy metals, it is also possible to reduce the elution of harmful substances such as heavy metals. In addition, while the procurement of sand, which is a natural resource, is limited, clinker ash is a by-product generated by coal-fired power generation, and its effective use leads to a reduction in waste and an effective use of resources.
[0011] The filler of the present invention is preferably such that the total content of the fly ash and cement is 35-55% by mass, and the content of the cement is 20-40% by mass, based on the total content of the clinker ash, fly ash, sand, and cement in the filler. Since the fly ash and cement are fine particles and have a binder function among the components of the filler of the present invention, in order to suppress bleeding while ensuring fluidity, the total content of the fly ash and cement relative to the total content of the clinker ash, fly ash, sand, and cement [(fly ash content + cement content) / (clinker ash content + fly ash content + sand content + cement content)] and the cement content relative to the total content of the fly ash and cement [cement content / (fly ash content + cement content)] are preferably within the above ranges. In addition, the cement content is 130 kg / m 3 The total content of the fly ash and cement relative to the total content of the clinker ash, the fly ash, the sand and the cement is more preferably 45 to 55 mass%, and further preferably 48 to 52 mass%. The content of the cement relative to the total content of the fly ash and the cement is more preferably 20 to 30 mass%.
[0012] The filler of the present invention contains clinker ash, fly ash, sand, cement and water, and the content of water relative to the total content of fly ash and cement is 150% by volume or less, so that the flow value is excellent in fluidity such as 150 mm or more, 180 mm or more, or 200 mm or more, while bleeding can be suppressed to 3% or less. The filler of the present invention can be produced by mixing the five components of clinker ash, fly ash, sand, cement and water so that the volume of water is 150% by volume or less relative to the total volume of the fly ash and cement to be mixed. In addition, a preferred embodiment of the filler of the present invention can be produced by further mixing the five components in the ratios described in the above paragraphs
[0009] to
[0011] . It can be produced by mixing in a predetermined ratio, and the mixing method is not particularly limited, and for example, an existing mixing method can be appropriately used. The filling method of the present invention is characterized in that, in the field of civil engineering and construction work, underground cavities and the like are filled with the filler of the present invention. For example, an existing filling method can be made into the filling method of the present invention by replacing the filler used with the filler of the present invention. EXAMPLES
[0013] [Examples 1 to 3] Fillers in Examples 1 to 3 were prepared with the mass blending ratios in Table 1. First, clinker ash, cement, fly ash, and sand were put into an 18L pail can, and dry mixing was performed with a hand mixer for 15 seconds. Next, premixed water and admixtures were put in, and the mixture was mixed with a hand mixer for 180 seconds to obtain a slurry-like filler. As the clinker ash, one in which particles with a particle size of 5 mm or less accounted for 80 mass% or more was used, and as the fly ash, fly ash raw powder was used. As the cement, ordinary Portland cement was used in Example 1, and blast furnace cement type B was used in Examples 2 and 3, and as the sand, mountain sand used for concrete that satisfied the JIS standard was used. As the admixture, a water-reducing agent conforming to the JISA6204 standard was used, and in Example 3, Chupol (registered trademark) EX60 (Takemoto Yushi Co., Ltd.) was used, and in the other Examples, Floric (registered trademark) SV10 (Floric Co., Ltd.) was used. The volume of water relative to the total volume of fly ash and cement, calculated by converting the blending ratios in Table 1 using specific gravity, was 147.8% in Example 1, 127.0% in Example 2, and 136.1% in Example 3. The properties of the resulting filler were measured by the following method. The measurement results are shown in Table 1. Regarding bleeding, a value between 3% and 5% was rated as "bad," and a value exceeding 5% was rated as "very bad." (Flow value) "Test method for air mortar and air milk" (φ80×h180mm cylinder method JHS A 313-1992) (Bleeding) Japan Society of Civil Engineers standard "Test method for bleeding rate and expansion rate of injection mortar for prepacked concrete" (JSCE-F522) (Selenium elution) Test solutions were prepared according to the method of Environment Agency Notification No. 46 of 1991, and analyzed according to the method of JIS K 0102.67.4. The ratio of the amount of elution of the obtained filler to the amount of elution of the fly ash raw powder (amount of elution of filler / amount of elution of fly ash raw powder) was taken as the selenium elution rate (%). (Elution of fluorine and fluorine compounds) The amount of elution from the fly ash raw powder was measured by spectrophotometry (JIS K 0102.34.1), and the amount of elution from the resulting filler was measured by ion chromatography (Announcement No. 59 of the Environment Agency in 1971, Appendix 7).
[0014] [Table 1]
[0015] [Comparative Examples 1 to 4] Fillers were prepared in the same manner as in the Examples using the mass blending ratios in Table 2, and their properties were evaluated. As for the water-reducing agent, Chupol EX60 (Takemoto Yushi Co., Ltd.) was used in Comparative Example 4, and Floric SV10 (Floric Co., Ltd.) was used in the other Comparative Examples. The volume of water relative to the total volume of the blended fly ash and cement, determined in the same manner as in the Examples, was 218.3% in Comparative Example 1, 147.8% in Comparative Example 2, 155.7% in Comparative Example 3, and 160.9% in Comparative Example 4. The measurement results are shown in Table 2. Regarding bleeding, a value between 3% and 5% was rated as "bad," and a value exceeding 5% was rated as "very bad."
[0016] [Table 2]
[0017] In the examples, a filler with excellent fluidity and bleeding suppression effects was obtained, with a flow value of 181 mm or more and bleeding of 3% or less. On the other hand, in Comparative Examples 1 and 2, in which sand was not used, bleeding exceeded 5% and separation of solids and water was large. In Comparative Example 1, since the water absorption of clinker ash is high, it is necessary to add a large amount of water to improve fluidity, and as a result, bleeding is large. In Comparative Example 2, even though the amount of water added was reduced, the bleeding characteristics were not improved much, and the flow value was low at 169 mm. In Comparative Examples 3 and 4, the volume of water relative to the total volume of fly ash and cement exceeded 150%, so fluidity was improved, but bleeding exceeded 5% and separation of solids and water was large.
[0018] Fillers were prepared in the same manner as in the examples with the mass blending ratios shown in Table 3 (water reducing agent Floric SV10 (Floric Co., Ltd.) was used). Heavy metals derived from fly ash are subject to the second type of specified hazardous substances specified in the Soil Contamination Countermeasures Act. Among them, selenium, fluorine and fluorine compounds are likely to exceed the elution standard, so the effect of clinker ash on the amount of elution of selenium, fluorine and fluorine compounds was measured. When the selenium elution rate of the fillers obtained in Example 2 and Reference Example 1 was measured, the selenium elution rate in Reference Example 1, which did not contain clinker ash but used fly ash, was 10.5%, while the selenium elution rate in Example 2, which contained clinker ash, was 9.5%, and the selenium elution rate was improved. In addition, in order to better show the effect of clinker ash on the amount of elution of fluorine and fluorine compounds, the elution amounts of fluorine and fluorine compounds are shown for the case where clinker ash is included in addition to fly ash and cement, and the case where sand is included in addition to fly ash and cement without clinker ash. The amount of fluorine and fluorine compounds eluted in Reference Example 2, which does not contain clinker ash, was 0.83 mg / L, whereas the amount of fluorine and fluorine compounds eluted in Comparative Example 2, which contains clinker ash, was 0.77 mg / L, which was below the environmental standard value of 0.8 mg / L. This shows that clinker ash reduces the amount of fluorine and fluorine compounds eluted, and the effect of clinker ash can be obtained in the filler of the present invention. In this way, by combining fly ash with clinker ash that does not contain many harmful substances and has a high pH, it is possible to suppress the elution of heavy metals, fluorine, and fluorine compounds (type 2 specific harmful substances) from fly ash and reduce the amount of elution. This is thought to be because these harmful substances are fixed by cement, but the amount fixed increases due to the action of clinker ash.
[0019] [Table 3]
[0020] [Example 4] The filler of Example 4 was prepared by the same method as in Examples 1 to 3 with the mass blending ratio in Table 4. The same clinker ash, fly ash and sand were used as in Examples 1 to 3. Blast-furnace cement type B was used as the cement, and Chupol (registered trademark) EX60 (Takemoto Yushi Co., Ltd.), a water-reducing agent conforming to JISA6204 standards, was used as the admixture. The volume of water relative to the total volume of the fly ash and cement calculated by converting the blending ratio in Table 4 based on specific gravity was 127.0%. The bleeding characteristics of the obtained filler when pressurized were measured by the following method. (Pressure bleeding test) The filler prepared in Example 4 was placed in a pressurizing container (Tsukuba Maruhigashi, inner diameter 125 mm, height 200 mm) to a height of 170 mm, and a hydraulic jack was used to pressurize the container so that the pressure inside the container became 0.14 MPa. This pressurized state was maintained for 5 minutes under non-draining conditions, and then bleeding was measured in the same manner as in the above-mentioned bleeding test.
[0021] As a result of the pressurized bleeding test, the bleeding rate of the pressurized sample was 2.0%. On the other hand, the bleeding rate of the filler prepared in Example 4 without pressurization was 2.5%, and the bleeding rate decreased by 0.5% due to pressurization. If the bleeding rate of the pressurized sample is Brp and the bleeding rate of the non-pressurized sample is Br, the bleeding occurrence rate Bro can be expressed as Brp / Br x 100 (%). In the above pressurized test result, the bleeding occurrence rate (Bro) was 80%. When the filler is poured, pressure is applied to the filler due to the weight of the filler itself. The pressure applied in the above pressurized test (0.14 MPa) corresponds to the pressure at a point of 0.809 m deep when the filler is poured. At a point of 0 m deep, that is, the pouring surface, no pressure is applied, so Brp and Br are equal, and Bro is 100%. With normal filler, the bleeding rate does not change much even when pressure is applied. In contrast, since the filler of the present invention contains clinker ash, which is a porous particle, it is presumed that the bleeding rate is reduced by water being taken into the pores of the particles due to pressurization. The filler of the present invention can suppress the occurrence of bleeding, and can suppress the occurrence of bleeding even when the casting lift (casting thickness) is thick. Since the bleeding rate decreases when the casting lift is made thicker, it can be suitably used for filling construction of a cavity with a ceiling such as a tunnel without using special additives such as foaming agents and expanding agents. For example, when the relationship between depth and Bro is derived and calculated from data of Bro being 100% at a depth of 0 m and Bro being 80% at a depth of 0.809 m, Bro drops to 50% when the depth reaches 2.1 m. Therefore, when the casting lift is set to 4.2 m, it is possible to reduce the overall amount of bleeding by 50%. (Calculation of pouring depth equivalent to pressurizing pressure) H=p / ρg=0.809m H is the pressure head, p is the pressure (0.14MPa = 0.14 × 10 6 N / m 2 ), ρ is the unit volume weight of the filler (1.76tf / m 3 =1.76×10 4 N / m 3 ), g=9.81
[0022] [Example 5] The filler of Example 5 was prepared by the same method as in Examples 1 to 3 with the mass blending ratio in Table 2. The same clinker ash, fly ash and sand were used as in Examples 1 to 3. Blast-furnace cement type B was used as the cement, and Chupol (registered trademark) EX60 (Takemoto Yushi Co., Ltd.), a water-reducing agent conforming to JISA6204 standards, was used as the admixture. The volume of water relative to the total volume of the fly ash and cement calculated by converting the blending ratio in Table 4 based on specific gravity was 130.3%. The properties of the obtained filler when cast underwater were measured by the following method. (Underwater casting test) Underwater sampling was performed using a Summit canister, which was submerged in a water tank and conformed to JSCE-F504-1990. Bucket sampling was performed by placing a plastic bag in a 7-L bucket, filling it with water to a depth of approximately 2.8 L (approximately 10 cm), and pouring in an equal amount of filler as the water.
[0023] A compressive strength test was conducted using specimens prepared by underwater sampling and specimens prepared by air sampling using a Summit can. The compressive strength was calculated as the average value of the three specimens. The result was 9.24N / mm 2 , 5.53N / mm when collected underwater 2 The compressive strength of both of these was 4N / mm. 2 The above was satisfied. In addition, each specimen obtained by air collection, underwater collection, and bucket collection was cut out and subjected to a leaching amount test. The results are shown in Table 5. The leaching amount was below the soil environmental standard in all of the air collection, underwater collection, and bucket collection. In this way, the filler of the present invention can make the leaching amount below the soil environmental standard without using an additive for suppressing the leaching of heavy metals, etc. In addition, selenium, fluorine, and fluorine compounds were measured by the method described in paragraph 0013, and chromium (VI) was measured in accordance with JIS K 0102.65.2.1, lead was measured in accordance with JIS K 0102.54.4, arsenic was measured in accordance with JIS K 0102.61.4, and boron was measured in accordance with JIS K 0102.47.4. In Table 5, "-" indicates less than the lower limit of quantification.
[0024] [Table 4]
[0025] [Table 5] [Industrial Applicability]
[0026] The filler of the present invention has excellent fluidity and suppresses the occurrence of bleeding, and therefore can be suitably used as a filler for civil engineering and construction work, including as a backfill material, an intermediate packing material, a backfill material, and an embankment material.
Claims
1. A cavity filling material for civil engineering and construction work, which is a mixture of clinker ash, fly ash, sand, cement and water, wherein the cement is Portland cement and / or blast furnace slag cement, and which satisfies the following (1), (2) and (3): (1) The content of the water relative to the total content of the clinker ash, the fly ash, the sand and the cement is 20 to 30 mass %. (2) A total content of the clinker ash and the sand is 45 to 55 mass% relative to a total content of the clinker ash, the fly ash, the sand, and the cement, and a content of the clinker ash relative to a total content of the clinker ash and the sand is 50 to 90 mass%. (3) The total content of the fly ash and the cement is 35 to 55 mass% relative to the total content of the clinker ash, the fly ash, the sand, and the cement, and the content of the cement relative to the total content of the fly ash and the cement is 20 to 40 mass%.
2. A method for producing a cavity filling filler for civil engineering and construction work by mixing clinker ash, fly ash, sand, cement and water, wherein the cement is Portland cement and / or blast furnace cement, and the clinker ash, fly ash, sand, cement and water are mixed in proportions that satisfy the following (a), (b) and (c). (a) The content of the water is 20 to 30 mass % based on the total amount of the clinker ash, the fly ash, the sand and the cement. (b) The total amount of the clinker ash and the sand is 45 to 55 mass% relative to the total amount of the clinker ash, the fly ash, the sand and the cement, and the total amount of the clinker ash is 50 to 90 mass% relative to the total amount of the clinker ash and the sand. (c) The total amount of the fly ash and the cement is 35 to 55 mass% relative to the total amount of the clinker ash, the fly ash, the sand, and the cement, and the total amount of the cement is 20 to 40 mass% relative to the total amount of the fly ash and the cement.
3. 2. A filling method comprising filling a cavity with the cavity filling material for civil engineering and construction work according to claim 1 into a cavity.
Citation Information
Patent Citations
Production of self-hardening filling-back material
JP1992182335A
Inside filler
JP1997227199A
Roadbed material
JP2003049401A
Cavity filler
JP2006069855A
Void filling material composition
JP2006160544A